ENHANCED SEMI-AUTOMATED BEHAVIORS FOR BUILDING CLEARING OPERATION OF MILITARY OPERATIONS IN URBAN TERRAIN IN KOREAN BATTLEFIELD ENVIRONMENT - Yoo, Seung Keun; Baik, Doo-Kwon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Global urbanization is increasing the influence of urban areas, while Military Operations in Urban Terrain (MOUT) is becoming increasingly in war. Critical engagements in recent wars have mainly occurred in urban areas. However, defense modeling and simulation in Korea has faced challenges in applying the characteristics of the urban terrain and MOUT to the analysis of force effectiveness. To overcome these issues, we enhanced in a One Semi-Automated Forces (OneSAF) simulation system the semi-automated behaviors for the building clearing operation (BCO), which is one of the most important operations in MOUT. Existing behaviors in OneSAF have limitations in applying detailed, actual actions of each combatant to the simulation. However, the enhanced behaviors can make the simulation more realistic. Through simulation experiments, we proved that these behaviors engender high fidelity in the simulation result, which can contribute to realistic and effective MOUT simulations.